Integrasi Dimensi Profil Pelajar Pancasila dalam Mata Pelajaran Pendidikan Agama Islam Menghadapi Era 4.0 di SMK Negeri Tambakboyo - Novita Nur ‘Inayah (CV. Gerasi Insan Nusantara, 2021)
The Industrial Revolution 4.0 has an impact on all lines of human life, including education. Education through the curriculum used is expected to be able to answer the challenges of the 4.0 era. The integration between the dimensions of Pancasila students and PAI subjects is the right formula in producing human resources who excel in science and technology, have religious, caring and nationalist characters.